Characterization of Thermally Stable Brønsted Acid Sites on Alumina‐Supported Niobium Oxide after Calcination at High Temperatures. Issue 11 (19th June 2013) - Kitano, Tomoyuki; Shishido, Tetsuya; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract Thermally stable Brønsted acid sites were generated on alumina‐supported niobium oxide (Nb2O5/Al2O3) by calcination at high temperatures, such as 1123 K. The results of structural characterization by using Fourier‐transform infrared (FTIR) spectroscopy, TEM, scanning transmission electron microscopy (STEM), and energy‐dispersive X‐ray (EDX) analysis indicated that the Nb2O5 monolayer domains were highly dispersed over alumina at low Nb2O5 loadings, such as 5 wt %, and no Brønsted acid sites were presents. The coverage of Nb2O5 monolayer domains over Al2O3 increased with increasing Nb2O5 loading and almost‐full coverage was obtained at a loading of 16 wt %. A sharp increase in the number of hydroxy groups, which acted as Brønsted acid sites, was observed at this loading level. The relationship between the acidic properties and the structure of the material suggested that the bridging hydroxy groups (NbO(H)Nb), which were formed at the boundaries between the domains of the Nb2O5 monolayer, acted as thermally stable Brønsted acid sites.